2021
DOI: 10.3390/ma14247512
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Different Alkali Metals in the A15Tl27 Type Structure and the Synthesis and X-ray Structure Analysis of a New Substitutional Variant Cs14.53Tl28.4

Abstract: Alkali metal thallides have been known since the report of E. Zintl on NaTl in 1932. Subsequently, binary and ternary thallides of alkali metals have been characterized. At an alkali metal proportion of approximately 33% (A:Tl~1:2, A = alkali metal), three different unique type structures are reported: K49Tl108, Rb17Tl41 and A15Tl27 (A = Rb, Cs). Whereas Rb17Tl41 and K49Tl108 feature a three-dimensional sublattice of Tl atoms, the A15Tl27 structure type includes isolated Tl11 clusters as well as two-dimensiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[18] During our research on the mixed A 15 Tl 27 phases, we observed the first ternary compounds in the K 49 Tl 108 type structure as a byproduct. [10] With an alkali metal proportion of approximately 33 % (A : Tl�1 : 2) its valence electron concentration is very similar to the one from A 15 Tl 27 (VEC�2.33) and therefore both phases are observed in the powder diffraction pattern (see SI).…”
Section: X-ray Structure Analysis From Single Crystalsmentioning
confidence: 85%
See 4 more Smart Citations
“…[18] During our research on the mixed A 15 Tl 27 phases, we observed the first ternary compounds in the K 49 Tl 108 type structure as a byproduct. [10] With an alkali metal proportion of approximately 33 % (A : Tl�1 : 2) its valence electron concentration is very similar to the one from A 15 Tl 27 (VEC�2.33) and therefore both phases are observed in the powder diffraction pattern (see SI).…”
Section: X-ray Structure Analysis From Single Crystalsmentioning
confidence: 85%
“…[9] The focus of our investigations is set on the different alkali metals, as they do not only serve as counterions for charge balancing reasons but play an essential role in the formation and stabilization of the thallium substructure. [2,10] One discrepancy becomes evident for the ratio of A : Tl 1 : 2. These materials are known to be metallic and a complete electron transfer from the electropositive to the electronegative element is virtually not true.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations